British support of the Dutch regime in West Irian at the onset of the cold war: Circumstance of 'evil necessity' - Ab Ghani, Rohani; Anwar, Od. M.; Mat Kib, Mat Zin (Asian Economic and Social Society, 2014)
This paper deals with the British policy on West Irian during the early stage of the Cold War in Southeast Asia. It focuses on the reasons why British supported the Dutch resolution to retain its colonial power on this ‘Komodo Island’.The main references are British official records from the British National Archive, Kew, London. Though they focus on British policy, the sources throw light on some of fundamental issues in Southeast Asia in general during that period.They prevail that although Western colonialization is a ‘taboo’ phrase, in some circumstances it was an ‘evil necessity.’First, British support for Dutch colonialism in West Irian was to prevent a circumstance that could allow any external intrusion such as the communist and Russian from setting up their base on that island which could endanger this region.The need for the Dutch colonialism was crucial because the newly formed Indonesia was still inexperienced in administering and managing territories.Secondly, it was a measure to eliminate any intention of Indonesia to spread, or to conquer, its neighboring nations such as Australia New Guinea, Borneo and the Malay States.In other words, should they were to be allowed to take West Irian it would become a precedent for Indonesia to make subsequent claims on other British territories.